Improving Grati 1.5 MWp Land-based Bifacial PV Production by Increasing Albedo with White Coral - Purwanto, Didik; Ridho, Muhammad Hafizh; Setyawan, Erwin (Department of Mechanical and Industrial Engineering, 2025)
Grati Combined Cycle Power Plant (CCPP) operates a Land-based PV with 1.5 MWp bifacial solar panel modules. Currently, the solar irradiance has not been absorbed optimally yet because the bottom surface of the bifacial has not been utilized. Therefore, it requires a material which functions to reflect the irradiance of the sun so that the bottom surface of the bifacial PV can absorb the irradiance. In this case, the white coral is chosen to apply as a reflector, due to its high albedo value, available and low price. This research aims to see how large the improvement of the white coral in increasing the Grati Land-based PV production. This research is to compare it with soil albedo through a literature study, field survey, PVsyst simulation and the calculation of actual increase percentage in PV production. Based on the measurement of PV production, the usage of white coral as a reflector below the bifacial panel can increase the PV production amounts 3.8% higher than the soil albedo.